(untitled) (Journal of Medicine, 2012)
Tuberculoma is not an uncommon lesion in intracranial space specially in developing world but tuberculoma in the cavernous sinus is very rare, and only less than ten cases have been reported in the literature, till today. Preoperative neuro-radiological features of such lesions may mimic neoplastic lesions of skull base and brain and post operative histopathological study brings the ultimate diagnosis. Here we report a rare case of cavernous sinus tuberculoma where tuberculomas were also in temporal lobe and Basal subarachnoid spaces (Right cavernous sinus, left temporal lobe, right sylvian fissure, basal cistern, interpeduncular cistern and prepontine cistern). DOI: http://dx.doi.org/10.3329/jom.v13i1.10056 JOM 2012; 13(1): 75-76 Tuberculoma is not an uncommon lesion in intracranial space specially in developing world but tuberculoma in the cavernous sinus is very rare, and only less than ten cases have been reported in the literature, till today. Preoperative neuro-radiological features of such lesions may mimic neoplastic lesions of skull base and brain and post operative histopathological study brings the ultimate diagnosis. Here we report a rare case of cavernous sinus tuberculoma where tuberculomas were also in temporal lobe and Basal subarachnoid spaces (Right cavernous sinus, left temporal lobe, right sylvian fissure, basal cistern, interpeduncular cistern and prepontine cistern). DOI: http://dx.doi.org/10.3329/jom.v13i1.10056 JOM 2012; 13(1): 75-76